Rethinking rangeland ecology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
During the 1980s the traditional rangeland sector suffered, perhaps more than any other, from what has frequently been described as the lost decade in terms of African rural development. Ranching schemes, enclosures, boreholes, mobile veterinary...